(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The article describes the economic essence of profit and the characteristics of the initial theoretical framework of its formation through the views of the manifestations of antiquity, as well as some economic schools, and the conclusions as a result of which are presented.